2021
DOI: 10.3390/cells10010056
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Tuning the Tumour Microenvironment: Current Perspectives on the Mechanisms of Tumour Immunosuppression

Abstract: Immunotherapy has revolutionised the treatment of cancers by harnessing the power of the immune system to eradicate malignant tissue. However, it is well recognised that some cancers are highly resistant to these therapies, which is in part attributed to the immunosuppressive landscape of the tumour microenvironment (TME). The contexture of the TME is highly heterogeneous and contains a complex architecture of immune, stromal, vascular and tumour cells in addition to acellular components such as the extracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 311 publications
0
15
0
Order By: Relevance
“…Immune effector cells in the TME can suppress tumor growth ( 19 ). However, tumor cells may escape immune surveillance, through various mechanisms such as polarizing monocytes and macrophages towards an M2 phenotype, creating tumor associated macrophages (TAMs), thereby suppressing cytotoxicity of antitumor immune cells ( 20 22 ). Although some of the immune infiltration cells including TAMs, natural killer cells, B cells, and regulatory T cells have no inhibitory effects on cancer cells, they influence the ability of tumors to escape immune attack ( 5 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Immune effector cells in the TME can suppress tumor growth ( 19 ). However, tumor cells may escape immune surveillance, through various mechanisms such as polarizing monocytes and macrophages towards an M2 phenotype, creating tumor associated macrophages (TAMs), thereby suppressing cytotoxicity of antitumor immune cells ( 20 22 ). Although some of the immune infiltration cells including TAMs, natural killer cells, B cells, and regulatory T cells have no inhibitory effects on cancer cells, they influence the ability of tumors to escape immune attack ( 5 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…In turn, therapies in which anti-PD-1, anti-PD-L1, or anti-CTLA-4 antibodies were combined with therapies aimed at reducing the activity of immunosuppressive cytokines such as TGF-β (tumour growth factor beta), M-CSF (macrophage-colony stimulating factor), and IL-10 seem to be less effective [ 81 , 82 ]. Addition of drugs blocking IL-10 or TGF-β function to classical immunotherapy increased the risk of adverse effects in the form of autoimmune reactions [ 83 , 84 , 85 , 86 ]. Nevertheless, clinical trials are underway to investigate the effectiveness of M7824—a fusion protein consisting of a human IgG1 monoclonal antibody against PD-L1 fused to the extracellular domain of the receptor for TGF-β, which captures TGF-β in the tumour environment [ 86 ].…”
Section: Use Of Non-specific Immune System Stimulation and Tumour Microenvironment Modification In Immune Combination Therapiesmentioning
confidence: 99%
“…The tumour microenvironment has a very adverse effect on the immune system functioning therein [ 83 ]. An unfavourable tumour microenvironment results in exclusion of immune response outside the tumour.…”
Section: Use Of Non-specific Immune System Stimulation and Tumour Microenvironment Modification In Immune Combination Therapiesmentioning
confidence: 99%
“…Like TAMS, MDSCs use a broad range of suppressive molecules to inhibit antitumor activity, including ARG1, iNOS, IDO, ROS, TGFβ and IL-10 [ 81 ]. We recently reviewed the dichotomous role these classically immune-suppressive molecules can play, focusing on both pro- and anti-tumoral effects in the TME [ 82 ]. In addition, it has been reported that MDSC can exert immunosuppressive effects via upregulation of PD-L1 [ 83 ], expression of the death receptor CD95 to induce T cell apoptosis [ 84 ] and production of MMP, which aid in tumour cell extravasation and migration [ 85 ].…”
Section: Cell Typesmentioning
confidence: 99%
“…Accordingly, many patients continue to respond poorly to standard of care therapies. It is well established that the immune system requires some degree of ‘fine-tuning’ to elicit effective and long-lasting anti-tumour immunity [ 82 ]. With the advancement of high-resolution omics technologies that encompass the global characterisation of DNA, RNA, chromatin accessibility, proteins and metabolites, new personalised treatment strategies can be developed to fine-tune these immune responses and improve individual patient outcomes ( Figure 1 ).…”
Section: Development Of Personalised Immunotherapies Guided By Integrated Omicsmentioning
confidence: 99%